Avaliação docente sob a ótica dos docentes e discentes: o caso de duas instituições de ensino superior privadas - Carneiro, Caroline (2016)
In pursuit of continuous quality improvement in education and to ensure a difference in the educational market, educational institutions concentrate an effort to track the performance of both their teachers and students. One of the tools used to monitor the performance of the teaching-learning process is the teaching evaluation, which is embedded in the institutional evaluation proposed by MEC, and seeks to identify the points that need attention throughout the teaching-learning process. Since this is a structured process, conducted within the institutions, this study aimed to identify the perception of teachers and students regarding the teacher evaluation process performed by two private institutions in Florianópolis, SC. In accordance with the nature of the objective, the methodology used was exploratory with a qualitative approach, and as a research strategy was conducted as a study case. Therefore, we used primary data collected through questionnaires and interviews, conducted from September to December 2015, with secondary data coming from the selection and bibliographic analysis. The results indicate that the institutions in this study have a highly structured and organized teacher evaluation process. In addition, it became clear that the two institutions are aware of the importance of teaching evaluation and its contribution to the improvement of teaching. During this study, there was evidence of the commitment of the professionals involved. Nevertheless, there was some noticeable rustle during the period in which the teacher assessment is applied by both teachers and students, but it was very punctual. Another factor that drew attention was the way that the data was collect by IES A, since there is a criticism of the tool used. This study sought to contribute to the literature on the subject researched, as well as within the society, since the analysis performed by the IES can serve as support for managers to improve their evaluation process.